Atividades investigativas para o ensino de óptica geométrica - Borrajo, Thiago Balacó (2017)
In the face of a scene of dissatisfaction and indifference in the process of teaching/learning of science in basic education, we present a proposal for teaching some fundamentals topics of geometrical optics, based on investigative activities that require reflection and reasoning. In it, the students are divided into groups and they need to discuss about ideas, make hypotheses and find ways for prove them. At the end of each class, the group conclusions are confronted with formal knowledge. Making it possible to analyze discrepancies and concordances with the know theory. The methodology is based on the concepts of active learning, sociointeractionism and inquiry based learning. The main focus of the proposal is increase student interest, make him more receptive to new knowledges by problematization and discussion with colleagues and teacher. With this method, it is possible to transform student into an agent in his own process of learning, developing his skills and capabilities in a science education process.